2015
DOI: 10.1152/ajpgi.00294.2014
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens extract ameliorates DSS-induced colitis by suppressing proinflammatory cytokines and inducing anti-inflammatory cytokines

Abstract: Urushima H, Nishimura J, Mizushima T, Hayashi N, Maeda K, Ito T. Perilla frutescens extract ameliorates DSS-induced colitis by suppressing proinflammatory cytokines and inducing anti-inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…As inflammatory mediators like TNF-α and IL-6 play critical roles in the pathogenesis of murine colitis, we analysed their expression by qPCR and Western blot. Consistent with previous reports [65][66][67][68][69][70], the levels of these pro-inflammatory cytokines in DSSinduced mice were found positively correlated to the severity of colitis in the current study. Furthermore, DAPP significantly provided suppressive effects on intrinsic TNF-α and IL-6 elevations under experimental colitis condition, which probably halts the pathological progression of pro-inflammatory cascade.…”
Section: Discussionsupporting
confidence: 93%
“…As inflammatory mediators like TNF-α and IL-6 play critical roles in the pathogenesis of murine colitis, we analysed their expression by qPCR and Western blot. Consistent with previous reports [65][66][67][68][69][70], the levels of these pro-inflammatory cytokines in DSSinduced mice were found positively correlated to the severity of colitis in the current study. Furthermore, DAPP significantly provided suppressive effects on intrinsic TNF-α and IL-6 elevations under experimental colitis condition, which probably halts the pathological progression of pro-inflammatory cascade.…”
Section: Discussionsupporting
confidence: 93%
“…While our study was in progress, Urushima et al (2015) reported that 0.54% PE administered for 7 days simultaneously with 1.5% DSS or for 10 days following 1.5% DSS treatment for 5 days ameliorated pathogenic symptoms of colitis in 8-week-old C57BL/6 female mice while it improved the body weight loss. They found that serum levels of TNF-α, IL-17A, and IL-10 were significantly reduced by co-administration of PE.…”
Section: Discussionmentioning
confidence: 69%
“…Luteolin suppressed production of proinflammatory cytokines, such as TNF-α, IL-1β, IL-6, and IL-17A in cultured monocytes derived from the 8-week-old wild-type C57/BL6 female mice. Apigenin also suppressed secretion of IL-17A while it increased the anti-inflammatory cytokine IL-10, whereas rosmarinic acid increased the regulatory T cell population ( Urushima et al, 2015 ). Rosmarinic acid has recently been shown to suppresses DSS-induced colitis which is attributed to its dual inhibition of NF-κB and STAT3 activation ( Jin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RA possess anti-inflammatory properties in carrageenan-induced paw oedema rat model and liver ischaemia-reperfusion and thermal injury rat models16. Furthermore, it has been reported that RA, as the biologically active element of Perilla frutescens , increases the regulatory T cell population in the DSS-induced colitis model17. However, there has yet to be a study evaluating the detailed in vivo biological efficacies of RA or demonstrating its underlying molecular mechanism in mice with DSS-induced colitis.…”
mentioning
confidence: 99%